'Does the picture below show a heterosexual couple or not?' Reflexivity, entextualization, scales and intersectionalities in a gay man's blog. (23rd June 2018) - Moita-Lopes, Luiz Paulo; Fabrício, Branca
Abstract : In this paper we investigate an intimate encounter in 'Life in the Closet', a blog fed by a Brazilian undergraduate, N.B., between 2011 and 2014. As a case in point, we focus on how a YouTube video advert called 'The Man Man' is successively entextualised in the blog, by following its re-entextualisation into posts made by the blogger himself and other participants. We explore this digital event as an instance of several chained reperformances, observing the highly reflexive activity that goes on in the blog and how such reflexivity operates through the friction of sedimented and transgressive discourses. By using a performative and scalesensitive approach to textuality and subjectivities, we fathom how participants reflexively queer gender, sexuality, age, race and social class by intersectionally making each one of these 'categories' dissolve its solidified meaning in the light of the Other as these meanings are called into being.